Accelerating Agriculture Productivity Improvement in Bangladesh: Mitigation co-benefits of nutrients and water use efficency - Nash, Julie; Grewer, Uwe; Bockel, Louis; Galford, Gillian L.; Pirolli, Gillian; White, Julianna M. (2016)
Analysis of potential mitigation in the development project Accelerating Agriculture Productivity Improvement (AAPI) in Bangladesh showed a 2% reduction in greenhouse gas (GHG) emissions, driven by urea deep placement (UDP) and alternate wetting and drying (AWD) in flooded rice systems. Given high emissions associated with conventional irrigated rice production, this represents a substantial reduction in emissions.  AAPI promotes UDP, a fertilization practice known to increase nitrogen uptake efficiency. Based on the project plan and progress of implementation, UDP adoption was anticipated on 1.1 million ha of aman rice and 700,000 ha of boro rice. UDP is an example of the absolute emission reductions that are possible when a practice is widely implemented.  AAPI promotes AWD, an irrigation practice for rice that reduces the amount of water used and results in decreased emissions. AAPI tested AWD on a pilot scale (21,000 ha). Climate change mitigation benefits would increase dramatically if adoption of AWD were more widespread.  Due to increased rice yields, UDP and AWD reduce the emission intensity (CO2e emitted per kg production) from rice production by 10–48%.